2020
DOI: 10.3390/sym12040655
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Sloshing Frequencies in Tanks with Structure Using New Presented DQM-BEM Technique

Abstract: The sloshing behavior of systems is influenced by different factors related to the liquid level and tank specifications. Different approaches are applicable for the assessment of sloshing behavior in a tank. In this paper, a new numerical model based on the differential quadrature method and boundary element approaches is adopted to investigate the sloshing behavior of a tank with an elastic thin-walled beam. The model is developed based on small slope considerations of the free surface. The main assumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This approach showed that the aileron has an impact on flutter speed and frequency. These investigations were compared with the numerical aero-elastic analysis, in further studies [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…This approach showed that the aileron has an impact on flutter speed and frequency. These investigations were compared with the numerical aero-elastic analysis, in further studies [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the hybrid structures is a common material which is widely employed in design [1], and analyzing [2][3][4][5][6][7][8] of various industrial engineering component with its specific bottlenecks and uncertainties. Since the advent of composite or metal-composite materials in aerospace structures, their applications have been steadily increasing.…”
Section: Introductionmentioning
confidence: 99%
“…A successful method to reduce the run-up as well as pressure peaks at the walls is the addition of additional structures inside the tank. This can be fixed inner structures [33][34][35][36][37] as well as potentially flexible elements [38]. Such a reduction of the impact of the sloshing is a next step planned for the floating cylinder.…”
Section: Introductionmentioning
confidence: 99%